2016
DOI: 10.1177/0148607116671101
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Dietary Fiber Ameliorates Radiation‐Induced Intestinal Epithelial‐to‐Mesenchymal Transition and Fibrosis

Abstract: The soluble dietary fiber pectin protected the terminal ileum against radiation-induced fibrosis. This effect might be mediated by altered SCFA concentration in the intestinal lumen and reduced EMT in the ileal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…It is characterized by down‐regulation in epithelial marker of E‐cadherin and an increase in mesenchymal markers of Vimentin and α‐SMA. It has been reported that radiation can induce EMT in a variety of tissues . Previous studies have also shown that the TGF‐β‐Smad3 signalling pathway plays an important role in radiation‐induced EMT .…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by down‐regulation in epithelial marker of E‐cadherin and an increase in mesenchymal markers of Vimentin and α‐SMA. It has been reported that radiation can induce EMT in a variety of tissues . Previous studies have also shown that the TGF‐β‐Smad3 signalling pathway plays an important role in radiation‐induced EMT .…”
Section: Discussionmentioning
confidence: 99%
“…The SCFA concentrations were determined by gas chromatography (GC) as previously described ( 37 ). Briefly, the feces from participants and cecal contents from mice were diluted, acidified, and extracted ultrasonically on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Myofibroblasts are activated by a variety of mechanisms including paracrine signals derived from immune and nonimmune cells, autocrine factors secreted by myofibroblasts, pathogen-associated molecular patterns derived from microorganisms that interact with pattern recognition receptors such as Toll-like receptors (TLRs), and the so called damage-associated molecular patterns derived from injured cells, including DNA, RNA, ATP, highmobility group box proteins, microvesicles, and fragments of ECM molecules (1, 14). The intestinal microbiota (15) (1618•) as well as dietary components (1921•) have been recognized to potentially modulate both intestinal inflammation and fibrogenesis. However, at present, neither specific bacterial strains nor specific micronutrients with pro-fibrotic or anti-fibrotic action have been clearly identified.…”
Section: Morphology and Mechanisms Of Intestinal Fibrosismentioning
confidence: 99%